Strategi Pengembangan Ekowisata Mangrove Wonorejo Surabaya - Khoirul Umam; Sudiyarto Sudiyarto; Sri Tjondro Winarno (Universitas Muhammadiyah Yogyakarta, 2015)
The aim of the research are to describe the potential of ecotourism development in mangrove forest, to describe the benefits that can be gained by the community, to analyze the internal and external environment in the development of Mangrove Ecotourism Surabaya, and to formulate development strategiy of Mangrove Ecotourism Wonorejo Surabaya based on internal and external environment. The first and second objectives were answered using descriptive analysis, while the third objective was answered using IFAS (Internal Factors Analysis Strategy) and EFAS (External Factors Analysis). The result showed that the Mangrove Ecotourism Wonorejo Surabaya has potential aspects to develop in referring to the ecology places/sutainability places, the natural resources including flora and fauna, the government support, the organizational, and the community of Wonorejo support for facilities and infrastructure. There are three aspects in terms of the benefit that owned by Mangrove Ecotourism Wonorejo Surabaya including social, economic and agribusiness aspects. Based on internal factors analysis (IFAS) and external factors analysis (EFAS), it was suggested that the aggressive strategy (growth), It can uses to get the opportunity strengthly, must be taken to develop mangrove ecotourism potential in Wonorejo, Surabaya.